Effects of estrogen deprivation on expression of aquaporins in rat vagina. Issue 8 (August 2015) - Zhu, Jiyin; Xia, Jiyi; Jiang, Jun; Jiang, Rui; He, Yanzheng; Lin, Haocheng
Abstract Objective This study aims to investigate the expression of aquaporin (AQP) 0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 in the vaginal tissue of ovariectomized rats. Methods Eight-week-old female Sprague-Dawley rats (n = 18) were randomly divided into three groups: control group (n = 6), ovariectomy group (n = 6), and ovariectomy/estrogen therapy group (n = 6). After 4 weeks, vaginal lubrication level and expression of AQP0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 in vaginal tissue were examined. Results Serum estrogen level was significantly lower in the ovariectomy group than in the control and ovariectomy/estrogen therapy groups (P < 0.05). Vaginal lubrication was significantly lower in the ovariectomy group (mean [SD], 1.62 [0.30]) than in the control group (mean [SD], 2.37 [0.70]) and ovariectomy/estrogen therapy group (mean [SD], 2.38 [0.73]; P < 0.05). Protein expression of AQP0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 was significantly lower in the ovariectomy group than in the control and ovariectomy/estrogen therapy groups (P < 0.05). Conclusions Decreased vaginal lubrication in ovariectomized rats after electrostimulation may be partly caused by decreased AQPs in vaginal tissue.